Longitudinal Associations between Emotion Regulation and Adiposity in Late Adolescence: Indirect Effects through Eating Behaviors - Shriver, Lenka H. (Nutrients, 2019)
The prevalence of obesity among U.S. youth continues to increase, with many adolescents engaging in unhealthy eating behaviors. Increasingly, research points to the role of self-regulation in obesity development, yet existing work has largely focused on young children and/or clinical adult populations. This multi-method longitudinal study (N = 153) utilized a path analysis to delineate links between emotion regulation (age 15), emotional eating and dietary restraint (age 16), and adiposity (% body fat) using a BodPod for body composition assessment (age 19). Emotion regulation was negatively associated with emotional eating (β = −0.30, p < 0.001) and positively associated with dietary restraint (β = 0.15, p < 0.05) at age 16, but was not associated with age 19 adiposity (β = −0.01, p = ns). Emotional eating was positively associated with adiposity (β = 0.24, p < 0.01). Indirect effects suggested that emotional eating, but not dietary restraint, at age 16 serves as a mechanism that helps explain the associations between emotion regulation and adiposity four years later. Results from this study suggest that both emotion regulation and emotional eating represent promising targets for that should be included in future interventions aimed at preventing adolescent obesity.